A Cu(ii) coordination polymer-based catalytic sensing system for detecting cysteine and sulfur anions. Issue 36 (5th September 2018) - Sun, Xiang-Ying; Qin, Zhen-Fa; Shen, Jiang-Shan; Cao, Xue-Gong; Liu, Bin; Wang, Huai-Qian
Abstract : Developing Cu(ii ) coordination polymer-based artificial enzyme mimics for establishing highly selective and sensitive sensing platform for Cys and S 2− anions. Abstract : Developing metal coordination polymer (CP)-based artificial enzyme mimics for establishing novel bio-chemosensing systems is important due to their high catalytic activity. Herein, a Cu(ii )-based CP (Cu-aspartic acid CP, that is Cu-Asp CP) was successfully prepared by a simple interface growth method. It was found that the as-prepared Cu-Asp CP has excellent peroxidase-like activity for 3, 3′, 5, 5′-tetramethylbenzidine (TMB) as the substrate in the presence of H2 O2 . On the basis of these findings, taken together with high complexing stability constants between Cu 2+ ions and cysteine (Cys)/S 2− anions, simple, highly sensitive and selective colorimetric assays for detecting Cys and S 2− anions were successfully developed, with low limits of detection estimated to be 0.625 μM and 0.206 μM, respectively.